2000
DOI: 10.4049/jimmunol.165.10.5767
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expressions of Toll-Like Receptor 2, But Not Toll-Like Receptor 4, Is Induced by LPS and Inflammatory Cytokines in Mouse Macrophages

Abstract: Toll-like receptors (TLRs) are a family of mammalian homologues of Drosophila Toll and play important roles in host defense. Two of the TLRs, TLR2 and TLR4, mediate the responsiveness to LPS. Here the gene expression of TLR2 and TLR4 was analyzed in mouse macrophages. Mouse splenic macrophages responded to an intraperitoneal injection or in vitro treatment of LPS by increased gene expression of TLR2, but not TLR4. Treatment of a mouse macrophage cell line with LPS, synthetic lipid A, IL-2, IL-15, IL-1β, IFN-γ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
181
5
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 256 publications
(223 citation statements)
references
References 49 publications
(31 reference statements)
33
181
5
4
Order By: Relevance
“…Cross-talk between TLR2 and TLR4 signaling pathways have been reported in murine macrophages and endothelial cells (Fan et al, 2003;Matsuguchi et al, 2000;Nilsen et al, 2004;Totemeyer et al, 2003). Interestingly, the effects in these cell types are in agreement to that what we observed for intestinal mIC cl2 epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cross-talk between TLR2 and TLR4 signaling pathways have been reported in murine macrophages and endothelial cells (Fan et al, 2003;Matsuguchi et al, 2000;Nilsen et al, 2004;Totemeyer et al, 2003). Interestingly, the effects in these cell types are in agreement to that what we observed for intestinal mIC cl2 epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, activation of TLR2 or TLR4 through commensal bacteria turns out to be a prerequisite for the protection against epithelial damage (Rakoff-Nahoum et al, 2004). For macrophages and endothelial cells, cross-talk between TLR2 and TLR4 resulting in alterations in TLR expression and/or function has been demonstrated (Fan et al, 2003;Matsuguchi et al, 2000;Nilsen et al, 2004;Totemeyer et al, 2003). Knowledge of the factors that control TLR expression and function in intestinal epithelial cells is still in its infancy but is crucial to facilitate future targeted modulation or restoration of intestinal homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we stimulated peritoneal mouse macrophages prepared from C3H/HeN mice with mouse TNF-␣ (40 ng/ml) for 3 or 16 h, which significantly increases TLR2 expression (43)(44)(45), before treatment with MG-132 and P3CSK4. Although the preactivation with TNF-␣ nearly doubled macrophage apoptosis in response to P3CSK4 (from 6 Ϯ 2% without TNF-␣ to 11 Ϯ 3% with TNF-␣ pretreatment after 8 h P3CSK4 stimulation), the overall degree of apoptosis remained moderate as compared with TLR4 responsive cell death.…”
Section: Tlr4 Potently Signals Agonist-dependent Apoptosismentioning
confidence: 99%
“…We have previously cloned the mouse TLR2 cDNA, analyzed its gene expression in immunocompetent cells, and reported that LPS and various cytokines including TNF-␣, IFN-␥, IL-1␤, IL-2, and IL-15 rapidly induce TLR2 gene expression in macrophages, whereas the gene expression of TLR4, another member of TLR, remains constant (14). We have also demonstrated that TCR engagement and the stimulation with IL-2 and IL-15 increase TLR2 mRNA in T cells.…”
mentioning
confidence: 99%